Disaster public health and older people - Chan, Emily Ying Yang, author.
1 online resource (xxii, 234 pages).
Keywords: "Disaster Public Health and Older People introduces professionals, students and fieldworkers to the science and art of promoting health and well-being, preventing diseases and prolonging life among the elderly in the context of humanitarian emergencies, with a particular focus on low and middle-income country settings. This book aims to make lessons learnt from previous disasters available and comprehensible to those working in disaster medicine, disaster public health, humanitarian studies, gerontology and geriatrics, empowering them to take the actions necessary at the individual, community and national levels to reduce the health risk to the elderly posed by disasters"--